One-pot three-component synthesis of some new azo-pyrazoline derivatives - Hawaiz, Farouq Emam; Hussein, Awaz Jamil; Samad, Mohammed Kareem (European Journal of Chemistry, 2014)
The starting material azo-benzyloxy acetophenone (2) has been synthesized in three steps; the direct diazotization of p-aminoacetophenone and its coupling reaction with m-cresol gave azo-acetophenone (1), which was benzylated with p-chlorobenzylchloride to give the starting material (2). The later compound was subjected to the one-pot three-component condensation reaction with substituted benzaldehydes and phenylhydrazine in the presence of sodium hydroxide to afford the target molecule azo-pyrazoline derivatives (3a-e) in high yields and short reaction times. The structures of the synthesized compounds were elucidated by using FT-IR, 1H NMR, 13C NMR and 13C DEPT 135 spectra.